WORKSHOP KEWIRAUSAHAAN: MENUMBUHKAN JIWA ENTERPRENEURSHIP GENERASI Z DI ERA KAMPUS MERDEKA - Yenni Agustina; Zakaria; Muslem Daud; Anwar; A Hamid; Ratna Mutia; Rizka; Herlina; Geta Ambartiasari; Dewi Mutia; Dedi Sufriadi (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2023)
The biggest challenge for students, including those at Serambi Mekkah University (USM), is that after completing their academic studies, they often assume they must either become employees at an institution or aspire to become Civil Servants (PNS) or work for large private companies in high-ranking positions to secure income or a salary. Therefore, there is a need for training to change the mindset of graduates or alumni from being job seekers to becoming job creators. This training/workshop activity took place at the Serambi Mekkah University campus in Banda Aceh. It was held for 3 days from December 20th to December 22nd, 2022. The program's partners or target participants were students from the Faculty of Education who already had or were planning to start a business, totaling 50 individuals. The implementation method included entrepreneurship development workshops covering preparation, understanding, training/workshops, mentoring, and evaluation. The outcome of this training was that participants gained an understanding of the importance of entrepreneurship for self-reliance. Through this PKM (Community Service Program), there was a noticeable increase in participants' understanding and interest in entrepreneurship.